Rehabilitation of Abandoned Housing Projects in Peninsular Malaysia: Reaching Out to Rescue Mechanisms in the Companies Act 2016 - Wai, Chen Thim (Emerald, 2022)
Purpose – In response to the housing needs of its people, Malaysia has allowed private housing developer companies to build houses on a sell-then-build basis. Despite having legislation designed to protect the interests of purchasers, insolvent housing developers have left behind many uncompleted housing projects with their land charged to financial institutions. Consequently, the affected purchasers will lose their houses when those financial institutions foreclose on the land in the housing projects. In addition, those purchasers remain legally obligated to repay loans taken to finance their house purchase. The housing development laws lack provisions to rehabilitate abandoned housing projects. The purpose of this paper is to explore the viability of rescue mechanisms in the Companies Act 2016, being corporate voluntary arrangement (CVA), judicial management (JM) and schemes of arrangement (SOA), to aid in the rehabilitation of abandoned housing projects in Peninsular Malaysia. Design/methodology/approach – Doctrinal research is adopted in this paper. Findings – This research highlights the flexibility of the SOA as a tool to rehabilitate abandoned housing projects. This research also reveals the potential of CVA and in particular, JM with its “public interest” feature, as useful rehabilitation mechanisms once the proposed reforms are adopted. Originality/value – The authors are hopeful that the suggested reforms will enhance the value of all three rescue mechanism s as rehabilitation tools for abandoned housing projects so as to alleviate the plight of house purchasers